Pengembangan Evaluasi Tes Objektif Menggunakan Aplikasi Quizizz Pada Subtema Keragaman Suku Bangsa dan Agama di Negeriku - Putri, Mutiara Jelita; Safitri, Nurlinda; Anjaswuri, Fitri (Jurnal Ilmiah Wahana Pendidikan, 2024)
The research uses the ADDIE development model, which includes five stages, with the aim of determining the feasibility and quality of developing an objective test evaluation using the Quizizz application with the sub-themes of ethnicity and religion. diversity in my country in carrying out the learning process for students at SDN Ciheuleut 2 Bogor City, the test in this development research is in the form of an expert validation test to test the feasibility of learning products so that they are suitable for use in the learning process and student response to the use of learning products. The results of the validation test carried out by the expert were media experts obtaining 92.5% with the criteria of "very feasible", linguists obtaining 90% with the criteria of "very feasible", and material experts obtaining 95% with the very feasible criteria of "very decent". While the results of the student response questionnaire obtained 85.2% in the "very good" category. Based on the results shown, it can be stated that the objective test evaluation learning product using the Quizizz application is very good and very feasible. Because it is more practical than conventional forms, it is effective for use in the learning process